Variations and Parallels in Climate Change-Induced Migration Models: Customary Land Tenure in Francophone Pacific Islands - Elisabeth Worliczek (Island Studies Journal)
It is tempting to assume that across all Pacific Islands, potential climate change-induced migration (PCCIM) due to sea-level rise can be approached in a unified manner. However, the diversity of the Pacific Islands requires an in-depth analysis in order to establish culturally coherent migration models. The possibilities and limits that customary land tenure can offer in this context on islands of the three Pacific French overseas territories Wallis & Futuna (Wallis, Futuna), French Polynesia (Rangiroa) and New Caledonia (Lifou) are analysed through four lenses: the intergenerational transfer of land rights, the distribution of land plots (geographically and between families), the extent of power exercised by customary authorities, and the different types of ownership or usufruct. The examination of common threads and variations shows that guiding principles (access to land in the interior of a respective island, strength of land rights on a certain plot, infrastructure issues, concepts of mobility, importance of primary land ownership, importance of primogeniture, and potential inter-island access) are shared to different degrees across the islands. The fourfold matrix allows a robust analysis of the possibilities in the context of PCCIM in different locations through examining parallels, differences, advantages, and disadvantages of the different systems.